1966
DOI: 10.1287/mnsc.12.12.b538
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Stockout Penalties

Abstract: Classical inventory theory considers that stockouts generate penalty costs to the firm, often assumed to be proportional to the excess of demand over supply. While such a concept is sometimes appropriate, it does not correctly reflect the effect of loss of goodwill. The latter is characterized by the fact that a disappointed customer reacts in the future to change his purchasing habits. Thus the nature of the effect is that subsequent demand is perturbed, a phenomenon quite different from having an immediate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

1974
1974
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 3 publications
1
34
0
Order By: Relevance
“…This paper provides empirical support to Schwartz's (1966) theoretical prediction that stockouts would alter future demand. As Anderson et al (2006) showed was the case with mail-order catalogs, we find that mobile money agents in Kenya and Uganda who stock out more often experience lower steady-state demand.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…This paper provides empirical support to Schwartz's (1966) theoretical prediction that stockouts would alter future demand. As Anderson et al (2006) showed was the case with mail-order catalogs, we find that mobile money agents in Kenya and Uganda who stock out more often experience lower steady-state demand.…”
Section: Discussionsupporting
confidence: 64%
“…The loss of future demand due to stockouts can be more difficult to estimate. Schwartz (1966) coined the term "perturbed demand" in his seminal work modeling the loss of consumer goodwill that a firm experiences in the aftermath of a stockout. "Perturbed demand" refers to the decrease in future demand, where this decrease is a function of the magnitude of the stockout.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…These papers include Schwartz (1966 and1970), Balcer (1980), Fergani (1976, and Robinson (1990). Conslik and Smallwood (1979) consider competition in the probability of a breakdown when firm quality choice is unobservable, a problem which is extremely similar to competition in service rates, however they also treat price and consumer behavior as exogenous.…”
Section: Introductionmentioning
confidence: 99%
“…In order to ensure a certain customer service-rate, we may introduce inventory holding costs and stock-out costs for the inventory of individual families (compare Tinarelli [52] and Schwarz [47]). …”
Section: Materials Coordinationmentioning
confidence: 99%